Exchange-Rate and Interest-Rate Driven Competitive Advantages in the EMU - Niclas Andrén; Lars Oxelheim (The Research Institute of Industrial Economics (IUI), 2002)
Real exchange and interest rates may still fluctuate inside the EMU and give rise to changes in competitiveness. We find, in contrast to what is generally expected, no convergence in these variables after the introduction of the euro. On the contrary, a divergence is found that is extraordinary when compared to the preceding 40 years. The magnitude of the divergence should urge on a wave of restructuring in the EMU, conditioned upon adequate policy responses. The worst-case scenario involves a flight to structural support and protectionism, challenging the whole idea of the EMU.
Keywords: E31; E44; F15; F23; G34; 330; Real Exchange Rates; Real Interest Rates; EMU; Competitive Advantage; Restructuring; Kaufkraftparität; Realzins; Eurozone; Internationaler Wettbewerb; EU-Staaten